What remains today of pre‐industrial Alpine rivers? Census of historical and current channel patterns in the Alps. (30th November 2020) - Hohensinner, Severin; Egger, Gregory; Muhar, Susanne; Vaudor, Lise; Piégay, Hervé
Abstract: To date, no survey on the diverse channel patterns existing prior to the major phase of river regulation in the mid‐19th–early 20th century has been elaborated at the scale of the whole European Alps. The present paper fills this knowledge gap. The historical channel forms of the 143 largest Alpine rivers with catchments larger than 500 km 2 (total length 11, 870 km) were reconstructed based on maps dating from the 1750s to 1900. In the early 19th century, one‐third of the large Alpine rivers were multi‐channel rivers. Single‐bed channels oscillating between close valley sides were also frequent in the Alps (28%). Sinuous and even more so meandering channels were much rarer. Historical river patterns generally followed an upstream–downstream gradient according to slope condition, floodplain width and distance from the sources. The local occurrence of certain channel patterns, however, primarily reflected the tectonic/orographic conditions. Multi‐channel reaches were widespread within the whole Alpine area, alternating with confined and oscillating reaches. This demonstrates that most areas were mainly transport‐limited rather than supply limited. Sinuous and meandering reaches were more frequent in the north‐eastern Alps and were characterized by lower denudation rates and less sediment delivery. Channel straightening caused the loss of about 510 km of river course length, equivalent to 4.3% of the historical extent. Multi‐channel stretches are currently a mere 15% of their historical length, and 45% of the larger Alpine rivers are intensively channelized or have been transformed into reservoirs. Channelization measures differed from one country to another. Human pressures directly affected both local channel geometry and the upstream controls (i.e., sediment supply). Accordingly, individual multi‐channel reaches also evolved into single‐thread channels without any local human interventions.